2016
DOI: 10.1002/pd.4938
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal compensatory renal growth in unilateral renal agenesis

Abstract: Cases of URA show a unique growth pattern of the single kidney from second trimester to term. Postnatal renal function is dependent on adequate intra-uterine compensatory growth; the presented nomograms provide insight into renal prognosis and add paramount information to the multidisciplinary prenatal counseling of the future parents. © 2016 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 27 publications
2
4
0
Order By: Relevance
“…Recently, compensatory hypertrophy was found in up to 88% of SFKs based on measurement of the kidney length . Perlman et al proposed a nomogram for renal length as a substitute for renal hyperplasia of SFK in fetuses with unilateral renal agenesis . In our study, we confirm this observation with 2D and 3D volume measurements.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Recently, compensatory hypertrophy was found in up to 88% of SFKs based on measurement of the kidney length . Perlman et al proposed a nomogram for renal length as a substitute for renal hyperplasia of SFK in fetuses with unilateral renal agenesis . In our study, we confirm this observation with 2D and 3D volume measurements.…”
Section: Discussionsupporting
confidence: 88%
“…29 Perlman et al proposed a nomogram for renal length as a substitute for renal hyperplasia of SFK in fetuses with unilateral renal agenesis. 30 In our study, we confirm this observation with 2D and 3D volume measurements. Compensatory hypertrophy is mostly seen as a physiological adaptation to the presence of only 1 functional kidney, and its absence is considered a less favorable sign for renal function at later age.…”
Section: Discussionsupporting
confidence: 87%
“…Van Vuuren et al 13 reported compensatory enlargement (defined as renal length > 95th percentile for gestational age [GA]) in 87% of MCDK cases and 100% of unilateral renal agenesis cases. Finally, a previous study published by our group 14 reported a unique growth pattern for solitary kidneys due to unilateral renal agenesis from the early second trimester to term.…”
mentioning
confidence: 59%
“…The percentile of the mean length of the normal kidney contralateral to the MCDK was compared to data regarding the solitary kidney length and percentile throughout gestation 14 with repeated measures for the second and third trimesters as mentioned above. The normal kidney contralateral to the MCDK had a significantly different compensatory growth pattern from the compensatory growth pattern of the solitary kidney as published in the literature (Table 3 and Figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…Unilateral renal agenesis causes intra-uterine compensatory renal growth, which can affect postnatal renal function [27]. MCDK can also cause compensatory hypertrophy of solitary functioning kidneys in utero [28].…”
Section: Discussionmentioning
confidence: 99%